Dynamic Crushing Strength Analysis of Auxetic Honeycombs - Hou, Xiuhui; Deng, Zichen; Zhang, Kai (Acta mechanica solida Sinica, 2016)
The in-plane dynamic crushing behavior of re-entrant honeycomb is analyzed and compared with the conventional hexagon topology. Detailed deformation modes along two orthogonal directions are examined, where a parametric study of the effect of impact velocity and cell wall aspect ratio is performed. An analytical formula of the dynamic crushing strength is then deduced based on the periodic collapse mechanism of cell structures. Comparisons with the finite element results validate the effectiveness of the proposed analytical method. Numerical results also reveal higher plateau stress of re-entrant honeycomb over conventional hexagon topology, implying better energy absorption properties. The underlying physical understanding of the results is emphasized, where the auxetic effect (negative Poisson’s ratio) induced in the re-entrant topology is believed to be responsible for this superior impact resistance.